Degree-of-interest trees: a component of an attention-reactive user interface - Stuart K. Card; David Nation (AVI'02: Proceedings of the Working Conference on Advanced Visual Interfaces, 2002)
This paper proposes Degree-of-Interest trees. These trees use degree-of-interest calculations and focus+context visualization methods, together with bounding constraints, to fit within pre-established bounds. The method is an instance of an emerging "attention-reactive" user interface whose components are designed to snap together in bounded spaces.